Praktik Jual Beli Baju Bekas Di Kota Tanjung Balai - Siregar, Elpida Sari (Jurnal El-Thawalib, 2022)
Buying and selling (Al-Bai') is a sale and purchase between objects and objects, or the exchange of objects for money, in this case the exchange of objects for money in other words the occurrence of a sale and purchase agreement that transfers the property rights of an object being traded, in this case it can be in the form of the benefits of clothing, food and housing including the needs of daily life. The problem in this research is how the practice of buying and selling used clothes in the city of Tanjung Balai in terms of the Sharia Economic Law Compilation. This research is field research or commonly called empirical normative research. Empirical normative or non-doctrinal research is research based on actual human behavior or actions and interactions. There are two sources of data, namely primary and secondary, while the data collection instruments are interviews, observation and documentation. This study found that the practice of buying and selling used clothes in the city of Tanjung Balai is something that is usually done by traders and consumers, the problem is the condition of objects being traded by traders where the object cannot be seen directly by buyers who want to resell. Because in the Compilation of Sharia Economic Law Article 76 explains the terms of the object being traded "Goods being traded must be known by the buyer" "The specifics of the goods being traded must be known". This explanation can be concluded that the terms of the object being traded have been regulated in the Compilation of Sharia Economic Law, and when buying and selling cannot be seen, the goods being sold are still in doubt, because of the element of gharar, namely the lack of clarity of the item.